Effectiveness of Leukocyte- and Platelet-rich Fibrin in the Management of Medication-related Osteonecrosis of the Jaws – A Systematic Review - Rahul Mohandas; Subhashree Mohapatra; Muskaan Singh; Supriya Kheur (Journal of Oral Research)
Background: Medication-related osteonecrosis of the jaw (MRONJ) is a rare, but significant adverse event primarily associated with the intake of antiresorptive and antiangiogenic medications. Although antiresorptive and antiangiogenic the-rapies improve life expectancy, particularly in cancer patients, MRONJ may hamper the patient’s quality of life due to pain, discomfort, anxiety, depression, speech impairment, difficulty in swallowing and eating, frequent medical and dental evaluations and treatments, and the possibility of treatment discontinuation. Leukocyte– and Platelet-rich Fibrin (L-PRF) is an autologous platelet aggregate that promotes wound healing by stimulating re-epithelialization, angiogenesis, and extracellular matrix production. Aim: The present systematic review aimed to compare the results in the published literature on whether L-PRF is an effective and predictable adjuvant to surgical debridement of necrotic bone for improving the healing efficacy in patients with MRONJ. Materials and Methods: The PubMed, Scopus, Cochrane, Science Direct, LILACS, and Web of Science databases were searched using the predetermined MeSH terms and eligibility criteria, and the search yielded a total of five articles. Two studies were retrospective, and three studies were case series. Results: Seventeen participants received a combination of surgical debridement, L-PRF membrane, and antibiotics. Complete wound healing was observed in 70% of the participants, and most of them healed without any complications. Conclusions: L-PRF as an adjuvant to surgical debridement of necrosed bone appears to have a positive association with the healing outcome in patients with MRONJ.